1996
DOI: 10.1002/hep.510240228
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis G: A Virus in Search of A Disease

Abstract: HEPATOLOGY Elsewhere 461 of HCV, the major population represented is interferon-sensi-ferent responses to IFN treatment. There were two groups: one consisted of nonresponders (n Å 63); the other consisted tive, but during or following IFN treatment in nonresponders, an IFN-resistant clone(s) constitutes the major population. of complete responders (n Å 21). The amino acid sequence analysis of the NS5A-ISDR indicated that there were three The difference was seen mainly in the E2, NS2, and NS5A regions in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The high frequency of GBV-C infection in fulminant hepatitis (50%) may reflect a higher rate of parenteral blood exposure in these patients rather than an etiologic relationship [40,43]. Although GBV-C virus was initially implicated in some cases of fulminant hepatic failure in children [40], we were unable to demonstrate this association in our patients, whether they had associated aplastic anemia or not [45•].…”
Section: Association Between Gbv-c Virus and Liver Diseasementioning
confidence: 80%
See 1 more Smart Citation
“…The high frequency of GBV-C infection in fulminant hepatitis (50%) may reflect a higher rate of parenteral blood exposure in these patients rather than an etiologic relationship [40,43]. Although GBV-C virus was initially implicated in some cases of fulminant hepatic failure in children [40], we were unable to demonstrate this association in our patients, whether they had associated aplastic anemia or not [45•].…”
Section: Association Between Gbv-c Virus and Liver Diseasementioning
confidence: 80%
“…In spite of the plethora of reports regarding GBV-C virus, evidence linking it to a specific liver disease or indeed, to any other illness, is still lacking [34]. GBV-C has been described in acute seronegative hepatitis (12%), cryptogenic chronic hepatitis (6%), cryptogenic cirrhosis (7%), hepatocellular cancer (25%), fulminant hepatic failure (50%), chronic hepatitis C (11%), and end-stage HCV-related cirrhosis before (24%) and after (28%) liver transplantation [36][37][38][39][40][41][42][43]. No studies, however, have demonstrated a GBV-Crelated histopathologic effect on the liver [38,41,42].…”
Section: Association Between Gbv-c Virus and Liver Diseasementioning
confidence: 99%